REGIONAL DIFFERENCES IN FEAR OF MISSING OUT AND STRESS AMONG NIGERIAN STUDENTS - Meek Ifeanyichukwu Eyisi; David Okechukwu Igbokwe, PhD (Journal of Social Science, 2026)
Objective: Fear of Missing Out (FOMO) and perceived stress have emerged as key indicators of student mental health in highly digitalised higher-education environments, yet little is known about how these constructs vary across regions and institutions within Nigeria. This study examined regional variations in FOMO and perceived stress among undergraduates drawn from public and private universities across the South-East, South-West and North-Central geopolitical zones. Method: A cross-sectional survey was administered to 4,930 undergraduates using structured questionnaires incorporating standard FOMO and perceived stress scales, alongside basic socio-demographic items. Data were analysed using descriptive statistics, cross-tabulations and one-way analysis of variance to compare FOMO across selected private universities. Results: FOMO was highly prevalent across all three zones: in each of the South-East and South-West, 89.3 % of students were classified as having FOMO, rising to 97.1 % in the North-Central zone. Perceived stress scores indicated a substantial stress burden across the sample, with most students reporting at least some level of stress. FOMO differed significantly across three private universities, with the South-East institution showing higher mean FOMO scores than the two South-West institutions. Both FOMO and perceived stress were widely distributed across socio-demographic subgroups, with concentrations among traditional-age undergraduates and a larger proportion of female respondents, but no strong demographic segmentation. Novelty: The findings indicate that FOMO and perceived stress are pervasive among Nigerian undergraduates and that regional and institutional contexts contribute to meaningful variation, particularly in FOMO. These results underscore the need for regionally sensitive and campus-specific interventions that address digital pressures and structural stressors simultaneously within Nigerian higher education.